Growing Teratoma Syndrome: A Rare Case Report and Review of the Literature - Nirmala Kampan; Trika Irianta; Arifuddin Djuana; Lim Pei Shan; Mohd Hashim Omar; Ahmad Zailani Hatta Mohd Dali (Case Reports in Obstetrics and Gynecology)
Growing teratoma syndrome is rare and usually it occurs in the younger aged group. The use of chemotherapy following initial surgical resection will yield the diagnosis following tumour enlargement. Complete resection is usually curative and renders better prognosis.